Molecular Cloning and Functional Characterization of Tibetan Porcine STING - Huang, Zhiqing (Molecular Diversity Preservation International (MDPI), 2012)
Tibetan pig is well known for its strong disease resistance. However, little is known about the molecular basis of its strong resistance to disease. Stimulator of interferon (IFN) genes (STING), also known as MPYS/MITA/ERIS/TMEM173, is an adaptor that functions downstream of RIG-I and MAVS and upstream of TBK1 and plays a critical role in type I IFN induction. Here we report the first cloning and characterization of STING gene from Tibetan pig. The entire open reading frame (ORF) of the Tibetan porcine STING is 1137 bp, with a higher degree of sequence similarity with Landrace pig (98%) and cattle (88%) than with chimpanzee (84%), human (83%) or mouse (77%). The predicted protein is composed of 378 amino acids and has 4 putative transmembrane domains. Real-time quantitative PCR analysis indicated that Tibetan pig STING mRNA was most abundant in the lung and heart. Overexpression of Tibetan porcine STING led to upregulation of IFN-β and IFN-stimulated gene 15 (ISG15) in porcine jejunal epithelial cell line IPEC-J2 cells. This is the first study investigating the biological role of STING in intestinal epithelial cells, which lays a foundation for the further study of STING in intestinal innate immunity.